EFFECTIVENESS OF THE PROBING PROMPTING MODEL ASSISTED BY KAHOOT GAMIFICATION ON STUDENTS’ MATHEMATICAL CONCEPTUAL UNDERSTANDING - Dwiyanti, Widya; Koswara, Ucu; Nuraeni, Annisa Suci; Darto, Darto (Journal of Authentic Research on Mathematics Education (JARME), 2026)
Limited conceptual understanding and low student engagement often hinder middle school learners in transforming contextual problems into formal mathematical representations. This study aims to evaluate the effectiveness of the Probing Prompting model assisted by Kahoot gamification in improving students’ mathematical conceptual understanding and to describe their attitudes toward its implementation. A quasi-experimental design was employed involving two seventh-grade classes with 23 students in the experimental group and 27 students in the control group. Data were collected through an essay test on conceptual understanding and a student attitude questionnaire. The results of the independent sample t-test showed a significant difference between the two groups, with the experimental class achieving an N-Gain score of 0.66 in the medium category, outperforming the control class, which obtained an N-Gain score of 0.28 in the low category. Students also demonstrated a positive attitude toward the integration of Kahoot, with an average score of 3.16. These findings indicated that the combination of structured probing questions and digital gamification was effective in strengthening students’ conceptual understanding while creating a more engaging and supportive learning experience.